Resection in the emergency of acute complications of colonic neoplasm - Asiner, Boris; Rodríguez de Vecchi, Victoriano; Balboa, Oscar (Cirugía del Uruguay, 2021)
The paper presents three cases of acute complications of colonic cancer which were treated by a primary resection and had a good evolution. This active therapeutical approach and its indications, are analyzed.